2020
DOI: 10.1186/s12863-020-00864-0
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome aberrations in pressure-induced triploid Atlantic salmon

Abstract: Background: Triploid organisms have three sets of chromosomes. In Atlantic salmon, hydrostatic pressure treatment of newly fertilized eggs has been extensively used to produce triploids which are functionally sterile due to their unpaired chromosomes. These fish often perform poorly on commercial farms, sometimes without explanation. Inheritance patterns in individuals subjected to pressure treatment have not been investigated in Atlantic salmon thus far. However, work on other species suggests that this treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 86 publications
1
22
0
Order By: Relevance
“…Over the past decade, we have conducted a number of pedigree-controlled studies on a multiple-generation experimental population of domesticated and wild Atlantic salmon and their crosses at the aquaculture facility owned by the Institute of Marine Research located in Matre, western Norway ( Solberg et al, 2013 , 2014 ; Ayllon et al, 2015 ; Harvey et al, 2016 , 2018 ; Glover et al, 2018 , 2020 ; Perry et al, 2019 ; Besnier et al, 2020 ). The reader is directed to these publications for full details regarding the standard rearing conditions experienced in this fish farm.…”
Section: Methodsmentioning
confidence: 99%
“…Over the past decade, we have conducted a number of pedigree-controlled studies on a multiple-generation experimental population of domesticated and wild Atlantic salmon and their crosses at the aquaculture facility owned by the Institute of Marine Research located in Matre, western Norway ( Solberg et al, 2013 , 2014 ; Ayllon et al, 2015 ; Harvey et al, 2016 , 2018 ; Glover et al, 2018 , 2020 ; Perry et al, 2019 ; Besnier et al, 2020 ). The reader is directed to these publications for full details regarding the standard rearing conditions experienced in this fish farm.…”
Section: Methodsmentioning
confidence: 99%
“…In diploid Atlantic salmon, reduced hypo-osmoregulatory ability during transfer to seawater creates loser fish, but these individuals survive up to harvest size, often retaining normal growth rates and condition factors after a period in seawater (unpublished personal results). Recently, Glover et al (2020) reported that triploid salmon display chromosomal aberrations. If the triploid loser fish phenomenon is related to osmoregulatory dysfunction, infections and/or genetic aberrations need to be further investigated to fully understand the suitability of triploid salmon in commercial aquaculture…”
Section: Discussionmentioning
confidence: 99%
“…While triploid embryos do produce a peak nuclear volume approximately 50% larger than that of diploids (as expected), the values are not normally distributed, extending into and below the modal volume of diploid embryos. This may reflect some degree of aneuploidy; indeed, recent work has demonstrated a high frequency of chromosomal aberrations in pressure‐induced triploid Atlantic salmon especially in cases when the rate of triploid induction is low (Glover et al, 2020).…”
Section: Discussionmentioning
confidence: 99%